Extraction of supernumerary nasal tooth by endoscopic approach - Tanzeem Ahmed; Samsuddin Ahmed; Nikhil Kaushal (Wolters Kluwer Medknow Publications, 2021)
The occurrence of the supernumerary tooth in the nasal cavity is uncommon. If not diagnosed and treated early, it may lead to various complications. Nasal endoscopy not only helps in proper diagnosis but also is an effective approach towards the extraction of the nasal tooth. It increases precision and reduces morbidity associated with the surgery.